Ekspresi C-kit dan Beberapa Faktor Klinokopatologis Karsinoma Payudara Subtipe Basal-like - Peter Santosa; Ahmad Ghozali (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2018)
Background Prognosis of breast cancer is determined by several factors such as age, tumor size, lymph node status, and histolopathological grade. Based on its molecular profile, breast cancer is divided into several subtypes and the basal-like subtype has the worst prognosis. Up to now, there is no appropriate and spesific therapy for that tumor. C-kit is a tyrosin kinase transmembrane receptor that has important roles in solid cancers development. C-kit can be expressed in normal breast duct epithelium and in breast cancer subtype with poor histopathological grade and prognosis. To find out about c-kit expression and the correlation with some clinicopathological factors in basal-like subtype breast cancer. Methods Paraffin embedded tissue of 301 infiltrating duct breast cancer patients from Anatomical Pathology Department of Sardjito General Hospital Yogyakarta year 2011-2013 were examined with immunohistochemistry staining, using monoclonal antibody anti ER, PR, HER2, CK5/6 and c-kit. The differences and association are analyzed using Independent T-Test, Fisher, and Kruskall Wallis statistics test. Results From January 2011-October 2013, there were 301 breast cancer patients with 87 of them (28,90%) were triple negative subtype (ER-. PR-. HER2-). Forty two triple negative cancers that match with inclusion criterias were stained with CK 5/6 to defined the basal-like subtype. There were 34 patients (81%) positive CK 5/6 expression (basal-like subtype) and 8 patients (19%) negative CK 5/6 expression (non basal-like). Patients with basal-like subtype have younger mean of age (p=0.026) and a bit larger tumor size but not statistically significant (p=0.560) compared with the non basal-like subtype. There were no significant correlation between basal-like subtype with age (p=0.052), tumor size (p=0.521), lymph node status (p=0.243), histopathological grade (p=0.115) and c-kit expression (p=0.118). Among the basal-like subtype group, 25 patients (73%) shared negative c-kit expression and 9 patients (27%) positive c-kit expression. There were no difference between positive and negative c-kit expression groups with age (p=0.434) and tumor size (p=0.267). There were no significant correlation between c-kit expression with age (p=0.544), tumor size (p=0.616), lymph node status (p=0.560), and histopathological grade (p=0.955). Conclusion C-kit expression could not be correlated to clinico-pathologic factor of basal-like subtype breast cancer. Key words : age, basal-like subtype breast cancer, c-Kit, histologic grade, lymph node status, tumor size.